The acute cross-education effect of foam rolling on the thigh muscles in patients after total knee arthroplasty - Yokochi, Masanobu; Nakamura, Masatoshi; Iwata, Ayaka; Kaneko, Ryota; Yamada, Noboru; Konrad, Andreas (Frontiers in Rehabilitation Sciences, 2024)
IntroductionIn the early postoperative period after total knee arthroplasty (TKA), joint range of motion (ROM) limitation and increased stiffness due to pain are commonly observed. Previous studies have reported that a single bout of foam rolling (FR) can acutely increase ROM and pain threshold on the contralateral (non-intervention) side in healthy participants. In this study, we aimed to expand this knowledge for TKA rehabilitation and investigated the acute effects of FR intervention on the non-operative side on ROM, stiffness, and pain of the operative side in postoperative patients within the first week after TKA.Materials and methodsThe study employed a randomized crossover design: 20 patients (mean age 75.0 ± 7.8 years) in the first postoperative week after TKA were divided alternately into Roll_Break and Break_Roll groups in the order of prescription. In the Roll_Break group, after the initial evaluation, a 180-s (60-s × three sets) FR intervention using a roller massager by a physiotherapist for the knee extensors was performed on the contralateral side (non-operative side), followed by the measurement. Afterwards, after 180-s of supine at rest, the measurement was performed again (i.e., control phase). In the Break_Roll group, after the initial evaluation, each patient was placed in a seated resting position for 180-s, and then another measurement was performed (i.e., control phase). After this, the FR intervention was performed for 180-s, and then the measurement was performed again. The intensity of the FR intervention was set to the maximum intensity that did not cause pain. We measured pain using the visual analogue scale at rest and during the knee joint ROM measurements, knee joint active movement ROM, knee joint passive ROM, and stiffness during the knee joint active movement.ResultsAll outcome variables showed significant improvements after the FR intervention (intervention phase) when compared pre- to post-intervention, and significantly favourable effects were found compared to the control condition.ConclusionThe results showed significant improvements in ROM, pain, and stiffness of the operative side after the FR intervention on the non-operative side. For future therapy approaches for TKA patients, FR treatment of the non-operative side should be employed in the first weeks after surgery.